Borohydride intermediates pave the way for magnesium-catalysed enantioselective ketone reduction - Vasilenko, Vladislav; Blasius, Clemens K.; Wadepohl, Hubert; Gade, Lutz H. (Chemical communications, 2020)
A magnesium precatalyst for the highly enantioselective hydro-boration of CO bonds is reported. The mechanistic basis of the unprecedented selectivity of this transformation has been investi-gated experimentally by isolation of catalytic intermediates and theoretically by DFT calculations. The facile formation of a magnesium borohydride species is critical in overcoming competing pathways in the selectivity-determining insertion step.
First published 20 December 2019
Gesehen am 24.02.2020